Time course of changes in immuneoendocrine markers following an international rugby game - Cunnife, B.; Hore, A. J.; Whitcombe, D. M.; Jones, K. P.; Baker, J. S.; Davies, B. (European Journal of Applied Physiology, 2010)
Intense exercise is known to cause temporary impairments in immune function. Few studies, however, have investigated the effects of intense competitive exercise on immunoendocrine variables in elite team sport athletes. The aim of this study was to evaluate the time course of changes in selected immunoendocrine and inflammatory markers following an international rugby union game. Blood samples were taken from players (n = 10) on camp entry, the morning of the game (pre), immediately after (post) and 14 and 38 h into a passive recovery period. Players lost 1.4 ± 0.2 kg of body mass during the game (ambient conditions, 11°C, 45% RH). An acute phase inflammatory response was observed as reflected through immediate increases in serum cortisol and IL-6 (post) followed by delayed increases in serum creatine kinase (CK; 14 h) activity and C-reactive protein (CRP; 38 h); P < 0.05. Decreases in the number of circulating T lympocytes, NK cells and bacteria-stimulated neutrophil degranulation were also observed post-exercise (P < 0.05), indicative of decreased host immune protection. Following a large decrease in serum testosterone to cortisol (T/C) ratio immediately post and 14 h after exercise, T/C values then increased above those observed at camp entry 38 h into recovery (P < 0.05). This rebound anabolic stimulus may represent a physiological requirement for recovery following intense tissue damage resulting from game collisions. The findings also suggest that a game of international rugby elicits disturbances in host immunity, which last up 38 h into the recovery period.